STRATEGI PENGEMBANGAN WISATA PANTAI YEH GANGGA MENJADI PRODUK WISATA BERDAYA SAING DI KABUPATEN TABANAN BALI - I Made Bayu Wisnawa; I Ketut Sutapa; I Gusti Agung Bagus Widiantara (Forum Manajemen, 2016)
This research has a specific purpose: (i) determine the potential ofcoastal area can be developed as a tourism product, (ii) Knowing constraints arefaced in developing the tourism potential, and (iii) determine strategies that can beused in developing the tourism potential of the coast as a creative tourism productsYeh Gangga Beach, Sudimara village, Tabanan Bali. The general objective to beachieved is to improve the performance of the tourism sector in the welfare ofsociety Tabanan through sustainable tourism development by developing creativepotential.. The research found that (i) Yeh Gangga Beach has some potential creativityattraction, such as: art market, handycraft,video and photography, music and artperformance, scenery, and accomodation; (ii) The main problems encounteredare (i) Most strategic land has been switched ownership to investors. The strategyshould be applied is (i) Maintain Yeh Gangga Beach as tourist attraction developedTabanan through local regulations, (ii) increasing public awareness of tourism. Theimplications are (i) theoretically enriching literature of sustainability in tourismcoastal area, (ii) practically could enhance the government to develop coastaltourism in Tabanan Bali.